Psychological features of emotional relationships in primary school teachers - Jabbarova Feruza Majidovna (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the psychological features of emotional relationships among primary school teachers, focusing on the mechanisms that influence teachers’ interactions with students, parents, and colleagues. It explores how emotional intelligence, empathy, and stress regulation contribute to building emotionally healthy learning environments and improving teachers’ professional effectiveness. Methodology: A mixed-methods approach was used, combining quantitative and qualitative data to ensure a comprehensive understanding of teachers’ emotional dynamics. The study involved 100 primary school teachers (aged 25–55) selected through stratified random sampling. Instruments included an Emotional Intelligence Questionnaire based on Goleman’s framework, the Teacher–Student Relationship Scale, classroom observations, and semi-structured interviews. Quantitative data were analyzed through correlation statistics, while qualitative data were examined thematically to identify patterns of emotional regulation, empathy, and stress management. Results: Findings revealed a strong positive correlation between emotional intelligence and the quality of teacher student relationships. Teachers demonstrating higher self-awareness, empathy, and emotional control experienced fewer conflicts, greater student trust, and higher job satisfaction. Gender and experience differences were also observed female and veteran teachers generally showed higher emotional resilience and relational stability. Conclusion: The study concludes that emotional intelligence is a vital component of teaching competence, shaping classroom climate, communication, and teacher well-being. Developing emotional awareness and regulation enhances both instructional quality and student outcomes. Limitations: The study was limited to one educational context and relied partly on self-reported data, which may influence objectivity. Contribution: This research contributes to educational psychology by emphasizing emotional competence as a core element of teacher professionalism and by providing practical insights for teacher training, counseling, and educational policy.